Teachers learning : professional development and education - McLaughlin, Colleen (Cambridge, UK : Cambridge University Press, 2013)
This book is part of The Cambridge Teacher series, edited by senior colleagues at the University of Cambridge Faculty of Education, which has a longstanding tradition of involvement in high quality, innovative teacher education and continuing professional development.
Includes bibliographical references and index.
Keywords: Teachers -- Training of; Teachers -- Training of -- Great Britain